ALC 2017 PLATFORM FOR GLOBAL PUBLIC/PRIVATE HIGHER INSTITUTIONS TO ENGAGE EXPERIENTIAL LEARNING IN LEADERSHIP AGENDA - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM PENANG, 11 January 2017 The Asia Leadership Conference (ALC) 2017, a oneday programme that is held today in Universiti Sains Malaysia (USM), gathers Asia Leadership Trekkers with 16 scholars from Harvard University, Northwestern, Tufts Fletcher School and National University of Singapore conducting a series of sessions on leadership.